Islanding detection for grid connected photo-voltaic systems for excess generation and under generation - E, Sunanda; spandana.S, Divya; Swapna, Ganapaneni (International Journal of Engineering and Technology, 2018)
Islanding occursÂ mostly in wide areas. The Dc-link-voltage method gives the effective results when compared to the Under/over Frequency/Voltage method and Rate of Change of Frequency (ROCOF) method. This paper describes the islanding detection based on observation of the DC-Link-Voltage Source Converter (VSC) and also proposes a method for detecting islanding for Grid-connected Photo-Voltaic system based on rise or fall of DC-Link-Voltage for excess generation and under generation conditions. The proposed technique is validated through experimental results.Â Â